Evaluation of Non-linear Models to Predict Potential Milk Yield of Beef Cows According to Parity Order Under Grazing - Ferreira, Matheus Fellipe de Lana; Rennó, Luciana Navajas; Rodrigues, Isabela Iria; Valadares Filho, Sebastião de Campos; Costa e Silva, Luiz Fernando; Silva, Fabyano Fonseca e; Detmann, Edenio; Paulino, Mário Fonseca (Frontiers in Veterinary Science, 2021)
Abstract This study aimed to evaluate the effect of parity order on MY and composition over time of grazing beef cows and to evaluate the equation from BR-CORTE in predicting MY. Thirty-six pregnant Nellore cows (12 nulliparous, 2 years; 12 primiparous, 3 years; and 12 multiparous, 4−6 years) were included in the study. Assigning calving day as day 0, milking was performed using a milking machine to estimate MY on days 7, 14, 21, 42, 63, 91, 119, 154, and 203. Dummy variable analyses were applied to estimate its effects on milk yield, composition, afternoon/morning, and afternoon/total proportions. The MY estimated by the BR-Corte (2016) equation was compared with the observed values from this study. The nonlinear model proposed by Cobby and Le Du (1978) was used to describe the lactation curve. The estimates for the parameters a, b, and c were compared between groups and the BR-Corte equation using model identity methodology. Nulliparous and primiparous displayed similar MY (P>0.05), however, multiparous cows had an average MY of 0.70 kg/d greater than nulliparous and primiparous (P<0.05). Milk fat and lactose did not differ between parities (P>0.05). Milk protein and total solids were different between parities (P<0.05), being higher for multiparous cows. Effect of days in milking was found for milk fat, protein and total solids (P<0.05). The afternoon/morning and afternoon/total proportion of milk production were not affected by parities and days in milking (P>0.05), with an average of 0.76 and 0.42, respectively. The BR-Corte equation did not estimate correctly MY (P<0.05). Thus, we recommend two different equations to estimate MY according to parity order. For Multiparous cows: MY = 7.927 - 0.095 x week - 7.927 x e (-1.502 x week) and for Nulliparous and Primiparous cows: MY = 6.613 - 0.053 x week - 6.613 x e (-2.129 x week), with estimated peak milk production of 7.56 and 6.48 kg, and time until the peak of 3.2 and 2.6 weeks, respectively. The parameters a, b and c, of the new equations were different from the BR-Corte parameters.